The effect of customer relationship management on bank performance: In context of commercial banks in Amhara Region, Ethiopia - Alemu Muleta Kebede; Zewdu Lake Tegegne (Cogent Business & Management, 2018)
This study examined the effects of Customer Relationship Management (CRM) practices on commercial banks performance in Amhara region, Ethiopia. However, the scarcity of research studies concerning CRM is still a major issue within the context of developing countries organizations like Ethiopia. Such research concept will help to improve the performance of the bank especially to improve the level of customers' satisfaction, which could be achieved by implementing best practices of CRM. For purpose of this study, dimensions of CRM practices are Key Customer Focus, Knowledge Management, CRM organization and Technology-Based CRM. The study deals with various factors influencing commercial banks, that is, Bank performance. These are Key Customer Focus, CRM organization, Knowledge Management and Technology-Based CRM. This study deployed Binary-Logistics regression model to analyze the effect of these factors on the performance of the bank. Customers of commercial banks were selected to fill self-administered questions related to CRM die response rate reached 94.4%. All dimensions of CRM considered in this study were found statistically significant (at p value of 0.05) in determining the performance of commercial banks. According to the binary regression result, Knowledge Management is more important factor in determining bank performances.
Keywords: 650